Parallel Continuous Double Auction for Service Allocation in Cloud Computing - Nima Farajian; Hossein Ebrahim pour-komleh (Universitas Sriwijaya, 2015)
Cloud Computing is a service oriented architecture in which every computing resources is delivered to users as a service. Nowadays market-oriented approach has attracted a lot of researchers because of its great ability to manage Cloud services efficiently and dynamically. Each service consists of various resources which all should be allocated to utilize the service. In this paper a parallel continuous double auction method for efficient service allocation in cloud computing is presented in which by using a novel parallel sorting algorithm at auctioneer, enables consumers to order various resources as workflow for utilizing requested services efficiently. Also in the presented method consumers and providers make bid and offer prices based on time factor. Experimental results show that proposed method is efficient in success rate, resource utilization and average connection time and also overall performance of system is improved by parallel approach.